2021
DOI: 10.1038/s41380-021-01335-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of problematic opioid prescription use in 132,113 23andMe research participants of European ancestry

Abstract: The growing prevalence of opioid use disorder (OUD) constitutes an urgent health crisis. Ample evidence indicates that risk for OUD is heritable. As a surrogate (or proxy) for OUD, we explored the genetic basis of using prescription opioids ‘not as prescribed’. We hypothesized that misuse of opiates might be a heritable risk factor for OUD. To test this hypothesis, we performed a genome-wide association study (GWAS) of problematic opioid use (POU) in 23andMe research participants of European ancestry (N = 132,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 62 publications
3
55
0
Order By: Relevance
“…Consistent with prior ndings, OUD showed strong genetic correlations with multiple substance use disorders, psychiatric disorders, cognitive traits, and risk behavior 13,15,16,63 . Mendelian randomization analyses demonstrated causal effects of OUD on problematic alcohol use and cannabis use disorder, and a bidirectional causal effect of drinks per week.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with prior ndings, OUD showed strong genetic correlations with multiple substance use disorders, psychiatric disorders, cognitive traits, and risk behavior 13,15,16,63 . Mendelian randomization analyses demonstrated causal effects of OUD on problematic alcohol use and cannabis use disorder, and a bidirectional causal effect of drinks per week.…”
Section: Discussionsupporting
confidence: 81%
“…Although these traits are known to be genetically correlated, it is unknown whether there is a shared genetic structure between OUD, other substance use, and psychiatric disorders. Negative r g 's were seen for educational attainment 13,15,16 , cognitive performance 13 and subjective wellbeing 16 . Causal effects on OUD for some of these traits were identi ed via Mendelian randomization (MR) analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent GWAS have increased sample sizes for genetic discovery by examining opioid-related phenotypes other than OUD. A GWAS of prescription opioid misuse in an EA sample from 23andMe (27,805 cases) identified 2 novel GWS loci 15 . A meta-analysis of European-ancestry individuals included 23,367 cases ascertained using either Diagnostic and Statistical Manual of Mental Disorders diagnoses (DSM) or frequency of opioid use (FOU) and 384,629 controls 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies also identified significant genetic correlations (r g 's) with traits well known to co-occur with OUD, suggesting widespread pleiotropy. The strongest positive r g 's were with substance-related traits (e.g., alcohol dependence/use disorder, cannabis use disorder, drinks/week, cigarettes/day) 12,13,15,16 , and psychiatric disorders (e.g., attention deficit hyperactivity disorder (ADHD), posttraumatic stress disorder (PTSD), major depressive disorder (MDD), schizophrenia, bipolar disorder, neuroticism) 13,15,16 . Although these traits are known to be genetically correlated, it is unknown whether there is a shared genetic structure between OUD, other substance use, and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%